Harapan dan Penilaian Industri Konstruksi terhadap Ketrampilan Lulusan Teknik Sipil - Musyafa, Albani (Unisia, 2012)
This research proposes to explore the quality of graduates of higher education in civil engineering in Australia. The result of the research can be used to help civil engineering education providers to apply a strategy to improve the quality of their graduates. The study uses primary data from the personal of construction industry, the data of which are analyzed statistically. This study reveals about the evaluation of the skill of civil engineering graduates by construction industry; the expectation of construction industry toward the skill which has to be mastered by graduates of civil engineering; and the gap between the evaluation and the expectation. Keywords: construction industry, skill of graduates, quality of graduates, civil engineering.